통일신라의 고주석 청동기에서 확인되는 제작기술의 다양성과 이에 투영된 사회적 변화에 관한 연구 - 박장식; Jang Sik Park; 주진옥; Jin Ok Joo (대한금속·재료학회지, 55(10), 2017)
Korea is famous for more than a millennium of continuous fabrication of Cu-Sn objects with near peritectic composition through a process of forging and rapid cooling at approximately 700 °C. We examined four high tin bronze hairpins excavated from two Unified Silla sites in Gyongju and found substantial variability reflecting the development process of high tin technology as it evolved toward a fully established and standardized state. This observation suggests two facts of significance; 1) the interest in high tin bronze technology was renewed or initiated with the coming of the Unified Silla and 2) the specific processing conditions gradually emerged from a long period of experimentation with various high tin alloys using a wide range of thermo-mechanical treatments. We discuss these two facts in terms of the plausible social transformations brought to Gyongju by Silla`s unification. The outcome will then be used to propose that the highly optimized and standardized high tin bronze tradition represents a technological innovation unique to Korea made possible by changing sociopolitical environments. (Received June 1, 2017; Accepted June 21, 2017)